2021
DOI: 10.1371/journal.pone.0250904
|View full text |Cite
|
Sign up to set email alerts
|

A novel diagnostic and prognostic approach for unresponsive patients with anthroponotic cutaneous leishmaniasis using artificial neural networks

Abstract: Cutaneous leishmaniasis (CL) imposes a major health burden throughout the tropical and subtropical regions of the globe. Unresponsive cases are common phenomena occurred upon exposure to the standard drugs. Therefore, rapid detection, prognosis and classification of the disease are crucial for selecting the proper treatment modality. Using machine learning (ML) techniques, this study aimed to detect unresponsive cases of ACL, caused by Leishmania tropica, which will consequently be used for a more effective tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Table 1 presents a summary of the studies that were analyzed as part of this research. Bamorovat et al [19] presented a Machine Learning-based approach to identify unresponsive cases of ACL caused by L.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents a summary of the studies that were analyzed as part of this research. Bamorovat et al [19] presented a Machine Learning-based approach to identify unresponsive cases of ACL caused by L.…”
Section: Resultsmentioning
confidence: 99%
“…In a time of restriction and contraindication for choice drug therapy, other drugs such as lipid formulations of amphotericin B (AmBisome ® ), paromomycin, miltefosine, ketoconazole, itraconazole, and fluconazole and also multiple therapies as a combination, could be used [31]. In general efficacy of MA against ACL, is high; however, cases of treatment failures (unresponsiveness) have been reported [25,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in artificial intelligence (AI) have revolutionized medicine, with machine learning (ML) algorithms and their identification capacity having an important application to help diagnosis [15][16][17][18]. Furthermore, dermatology has benefited from novel diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies applying ML to diagnose dermatoses caused by infectious agents such as Leishmania. Bamorovat et al [18], presented a new diagnostic and prognostic method for classifying CL including responsive and non-responsive patients, showing the potential for automatic identification of leishmaniasis using ML algorithms. Furthermore, Noureldeen et al [27], showed a new diagnostic method of CL detection and classification with an ML model.…”
Section: Introductionmentioning
confidence: 99%